Case report: Early (molecular) diagnosis is the clue: report on ALDH7A1 deficiency in newborns - Lipiński, Patryk; Wójcicka-Kowalczyk, Katarzyna; Bogdańska, Anna; Ehmke, Ewa; Pajdowska, Magdalena; Skrzypek, Katarzyna; Charzewska, Agnieszka; Hoffman-Zacharska, Dorota (Frontiers in Genetics, 2024)
The first-tier geneting testing for developmental and epileptic encephalopathies (DEE) is now increasingly used in routine clinical practice. Antiquitin deficiency, also referred to as pyridoxine-dependent epilepsy (PDE-ALDH7A1), represents an inherited metabolic disorder with the phenotype of an early-infantile DEE. Besides the fact that biochemical biomarkers of PDE-ALDH7A1, including α-aminoadipic semialdehyde dehydrogenase, pipecolic acid (PA), Δ1-piperideine-6-carboxylate, and 6-oxopipecolate (6-oxo-PIP) are well characterized, their analysis and usefulness have some limitations. Here we describe the case of a newborn presenting with seizures from the first hours of life, resistant to standard antiepileptic drugs, who was found to be a biallelic compound heterozygote of two clearly pathogenic variants in ALDH7A1 gene based on targeted next generation sequencing (NGS). The diagnostic process of PDE-ALDH7A1 was limited by the possibility to determine only urinary PA and 6-oxo-PIP (urinary organic acid profile using GC-MS method) and the exogenous peak of levetiracetam, due to the fact that it has a similar retention time as 6-oxo-PIP, masked the detection of 6-oxo-PIP.